Building competency to deal with environmental health challenges: experiences and a proposal - Giovanni S. Leonardi; Giovanni S. Leonardi; Ariana Zeka; Ariana Zeka; Matthew Ashworth; Matthew Ashworth; Catherine Bouland; Helen Crabbe; Raquel Duarte-Davidson; Ruth A. Etzel; Nia Giuashvili; Özden Gökdemir; et al. (Frontiers Media S.A., 2024)
The global landscape of professional training in environmental health, encompassing ecological public health or environmental public health, lacks consistent global implementation for training programs for public health practitioners, clinical professionals, and individuals across various disciplines, as well as standardized curricula for undergraduates. This training gap is related to the overall lack of capacity in addressing the population impacts of the triple challenge of pollution, biodiversity loss, and climate change, impeding the worldwide transition to and development of ecological sustainability. This paper reviews existing approaches and their potential to address implementation challenges within the necessarily tight timescale. Spreading of best practice appears feasible even without substantial additional resources, through the reorientation of current practices via comprehensive multi-disciplinary training programs. By adopting international best practices of training in environmental health, the focus in training and education can shift from future decision-makers to enhancing the competencies of current professionals and their institutions.